Optimization of the Imposition of Additional Compensation Penalties for Corruption Crimes that Harm State Finances Due to the Alternative Choice of Imprisonment as a Substitute (Study of Decision Execution in North Maluku in 2021) - Setiawan, Heri; Malik, Faissal; Anshar, Anshar (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research aims to analyze the optimization and effectiveness of imposing additional fines as a substitute for imprisonment in relation to the execution of judgments in North Maluku in 2021, specifically focusing on corruption offenses that harm the state finances. The study employs an empirical legal research approach, utilizing empirical data obtained from interviews and direct observations of human behavior. Three approaches are utilized in this research: legal, conceptual, and case-based approaches. The research findings indicate that the imposition of additional fines as a substitute for imprisonment in corruption cases that harm state finances is still not optimal. Out of the seven cases examined, only two cases resulted in the restitution of the state's financial losses. Furthermore, the research highlights the failure to achieve legal effectiveness due to the insufficient restitution of state financial losses resulting from the availability of the alternative option of imprisonment as a substitute for the additional fines.